Mechanical Fractionation of Adipose Tissue—A Scoping Review of Procedures to Obtain Stromal Vascular Fraction - Schipper, Jan; van Laarhoven, Constance; Schepers, Rutger; Tuin, A.; Harmsen, Marco; Spijkervet, Fred; Jansma, Johan; van Dongen, Joris (Bioengineering (Basel), 2023)
Clinical indications for adipose tissue therapy are expanding towards a regenerative-based approach. Adipose-derived stromal vascular fraction consists of extracellular matrix and all nonadipocyte cells such as connective tissue cells including fibroblasts, adipose-derived stromal cells (ASCs) and vascular cells. Tissue stromal vascular fraction (tSVF) is obtained by mechanical fractionation, forcing adipose tissue through a device with one or more small hole(s) or cutting blades between syringes. The aim of this scoping review was to assess the efficacy of mechanical fractionation procedures to obtain tSVF. In addition, we provide an overview of the clinical, that is, therapeutic, efficacy of tSVF isolated by mechanical fraction on skin rejuvenation, wound healing and osteoarthritis. Procedures to obtain tissue stromal vascular fraction using mechanical fractionation and their associated validation data were included for comparison. For clinical outcome comparison, both animal and human studies that reported results after tSVF injection were included. We categorized mechanical fractionation procedures into filtration (n = 4), centrifugation (n = 8), both filtration and centrifugation (n = 3) and other methods (n = 3). In total, 1465 patients and 410 animals were described in the included clinical studies. tSVF seems to have a more positive clinical outcome in diseases with a high proinflammatory character such as osteoarthritis or (disturbed) wound healing, in comparison with skin rejuvenation of aging skin. Isolation of tSVF is obtained by disruption of adipocytes and therefore volume is reduced. Procedures consisting of centrifugation prior to mechanical fractionation seem to be most effective in volume reduction and thus isolation of tSVF. tSVF injection seems to be especially beneficial in clinical applications such as osteoarthritis or wound healing. Clinical application of tSVF appeared to be independent of the preparation procedure, which indicates that current methods are highly versatile.